EVALUASI PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN 24 IMBALAN KERJA PADA PT. DOS NI ROHA MANADO - Sulangi, Pricilia; Karamoy, Herman (Universitas Sam Ratulangi, 2021)
Employee Benefits are all forms of compensation provided by the entity in exchange for services rendered by employees, including directors and management. There are 4 types of employee benefits, namely short-term employee benefits, other long-term employee benefits, post-employment benefits, and severance pay. Employee benefits are regulated in the Statement of Financial Accounting Standards (PSAK) 24 Employee Benefits. The purpose of this study is to evaluate the application of employee benefits at PT. Dos Ni Roha Manado in accordance with the provisions of PSAK 24 Employee Benefits. This study uses qualitative analysis methods and research data obtained through interviews. The results of this study indicate the employee benefits applied by PT. Dos Ni Roha Manado is a short term employee benefit. Recognition, measurement and presentation of short-term employee benefits in accordance with PSAK 24.